2013
DOI: 10.1371/journal.pone.0066408
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Absorption of a New Riboflavin-Nanostructured System for Transepithelial Collagen Cross-Linking

Abstract: Corneal collagen cross-linking (CXL) has been described as a promising therapy for keratoconus. According to standard CXL protocol, epithelium should be debrided before treatment to allow penetration of riboflavin into the corneal stroma. However, removal of the epithelium can increase procedure risks. In this study we aim to evaluate stromal penetration of a biocompatible riboflavin-based nanoemulsion system (riboflavin-5-phosphate and riboflavin-base) in rabbit corneas with intact epithelium. Two riboflavin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 41 publications
1
29
0
Order By: Relevance
“…Other methods, investigated in rabbit corneas, include: phonophoresis (ultrasound-assisted drug penetration) and a biocompatible riboflavin-based nanoemulsion system. Both have shown potential in increasing transepithelial penetration of riboflavin [80,81]. Lastly, the use of a hypoosmolar riboflavin solution (with 0.44% NaCl) was also investigated and appears to contribute to the transepithelial absorption of riboflavin [74].…”
Section: Evolution Of Riboflavin: Uva Corneal Collagen Crosslinkingmentioning
confidence: 99%
“…Other methods, investigated in rabbit corneas, include: phonophoresis (ultrasound-assisted drug penetration) and a biocompatible riboflavin-based nanoemulsion system. Both have shown potential in increasing transepithelial penetration of riboflavin [80,81]. Lastly, the use of a hypoosmolar riboflavin solution (with 0.44% NaCl) was also investigated and appears to contribute to the transepithelial absorption of riboflavin [74].…”
Section: Evolution Of Riboflavin: Uva Corneal Collagen Crosslinkingmentioning
confidence: 99%
“…Moreover, as mentioned earlier, the eye is not an easily accessible organ mainly due to the constant presence of nasolacrimal drainage and corneal barrier 16 . In this context, the MEs are presented as an interesting therapeutic alternative for the ophthalmic route.…”
Section: Development and Preparation Of Microemulsions For Use In Thementioning
confidence: 99%
“…Bottos et al 33 have previously demonstrated that 0.5% riboflavin-5-phosphate nanoemulsion could penetrate efficiently in the stroma of rabbit eyes through the intact epithelium, however, after 2 hours of soaking time. Although the results were comparable to standard stromal soaking, the long soaking time makes the methodology unsuitable for clinical use; in addition, the authors did not provide any information on the stromal stiffening induced by UV-A irradiation of the rabbit cornea.…”
Section: 27-29mentioning
confidence: 99%